Codex Alimentarius Commission : (Food and Agirculture Organization of the United Nations, 2005)
The FAO/WHO Codex Alimentarius Commission is the unique United Nations body responsible for establishing international food standards aimed at protecting the health of consumers and ensuring fair practices in the food trade. The food standards, codes of practice, and other guidelines and recommendations adopted by the Commission form the Codex Alimentarius: the international food code. The Codex Alimentarius Commission envisages a world afforded the highest attainable levels of consumer protection, including food safety and quality.